Digital Health Information Systems and Patient-Centered NCD Promotion: A Systematic Review - Jumriyanti Nasaru; Mahalul Azam; Oktia Woro Kasmini Handayani; Ari Yuniastuti (Jurnal Kesehatan Masyarakat, 2026)
The Non-communicable diseases (NCDs) account for 71% of global deaths and require digital transformation in management at the primary healthcare level. Analyze the impact of digital health information systems on the effectiveness of patient-centered health promotion strategies for NCDs in public health clinics. The Systematic Literature Review uses the PRISMA 2020 methodology with searches on 7 electronic databases (Scopus, ScienceDirect, Frontiers, SpringerLink, Heliyon, Taylor & Francis, PubMed) for the period 2020-2025. Of the 309 articles identified, 40 studies met the inclusion criteria. Digital platforms integrated with robust eHealth infrastructure indicate significant effectiveness in improving patient health outcomes, with hypertension control reaching 59% and mental health improvement up to 86%. Patient-centered communication and eHealth are key moderators in increasing patient engagement. The implementation of digital health information systems has a positive impact on patient-centered health promotion for NCDs. A systemic approach that integrates technology, human resources, and comprehensive policies is needed to optimize digital health transformation at the community level.